Utilization of neem leaf extract (Azadirachta indica A. Juss.) in inhibiting the growth of acne-causing bacteria Cutibacterium acnes - Sinatra, Dhimas Pramayoga; Rini, Chylen Setiyo (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2026)
Background: Acne is an infection that occurs on the surface of the skin in the form of inflammation of the oil glands in the epidermal layer of the skin, when infected by the bacteria Cutibacterium acnes, blackheads will develop into inflammation and cause acne vulgaris. One of the plants that can be used as a natural alternative in acne treatment is neem (Azadirachta indica A. Juss). Objectives: This research aims to identify the inhibitory effect of neem leaf extract on C. acne. Materials and Methods: Neem leaves samples were obtained from the Sumenep district. The research was conducted at the PIPOT-UBAYA Laboratory, the Pharmacy Laboratory of PGRI Adi Buana University Surabaya and the Microbiology Laboratory of Stikes Ngudia Husada Madura. The research design used is experimental, testing of the inhibition power of neem leaves using the diffusion method by observing the inhibition zone around the disc. This research used concentrations of 25, 50, 75, and 100%. The positive and negative controls used are sterile aquades and Clindamycin. Results: The results showed the inhibition zones of neem leaf extract against C. acnes at concentrations of 25% and 50% were 6.3 mm and 9.3 mm, while at concentrations of 75% and 100% were 12.3 mm and 16 mm. Conclusions: The results of the one-way ANOVA test showed p-value is 0.000, which means that neem leaves can inhibit the growth of C. acnes.